2013
DOI: 10.1016/j.bbamem.2013.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics perspective on rhomboid intramembrane protease evolution and function

Abstract: Endopeptidase classification based on catalytic mechanism and evolutionary history has proven to be invaluable to the study of proteolytic enzymes. Such general mechanistic- and evolutionary- based groupings have launched experimental investigations, because knowledge gained for one family member tends to apply to the other closely related enzymes. The serine endopeptidases represent one of the most abundant and diverse groups, with their apparently successful proteolytic mechanism having arisen independently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Reciprocal BLAST analysis and secondary structure similarities detected by HHPred38 indicate that two of the proteins, termed TimRhom I and TimRhom II, belong to the rhomboid family of proteins. This protein family consists of not only intramembrane proteases that are conserved in all domains of life3940 but also includes a growing group of rhomboid-like proteins that are proteolytically inactive41. TimRhom I and TimRhom II belong to the latter group, since the Ser-His catalytic dyad is not conserved (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reciprocal BLAST analysis and secondary structure similarities detected by HHPred38 indicate that two of the proteins, termed TimRhom I and TimRhom II, belong to the rhomboid family of proteins. This protein family consists of not only intramembrane proteases that are conserved in all domains of life3940 but also includes a growing group of rhomboid-like proteins that are proteolytically inactive41. TimRhom I and TimRhom II belong to the latter group, since the Ser-His catalytic dyad is not conserved (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The situation for the presequence translocase of T. brucei is quite different, since, besides TbTim17, its essential core includes the rhomboid-like proteins TimRhom I and TimRhom II. Rhomboid-like proteins are found in all three domains of life including α-proteobacteria40. Since TimRhom I and TimRhom II are not closer related to eukaryotic rhomboid-like proteins (for example, derlins, PARL) than to their bacterial counterparts, they may have been commandeered from the original endosymbiont that gave rise to mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the bacterial rhomboids with the 6 + 1 TM helices could either be a bacterial progenitor to the eukaryotic rhomboid proteases or they may represent an ancient family of rhomboid proteases present in the last universal common ancestor (LUCA) [45]. The fact that family A (6 + 1 TM topology) and family D (6 TM topology) are present in all genomes analyzed suggests that each family could have different and potentially critical biological roles in Streptomyces .
Figure 3Transmembrane structure of Rhomboids using TMRPres2D [45]. Rhomboids a , b , c and d are from S. coelicolor , and e is from S. sviceus active sites are highlighted with a red circle.
…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Kinch and Grishin take us back to the beginning by reconsidering rhomboid protease evolution [24]. Intramembrane proteases are nearly ubiquitous enzymes across all life forms, presenting a wealth of biological settings for analysis, yet complicating evolutionary interpretations.…”
Section: Part Iv: Emerging Topicsmentioning
confidence: 99%